Second Assessment of Climate Change for the Baltic Sea Basin - The BACC II Author Team.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book is an update of the first BACC assessment, published in 2008. It offers new and updated scientific findings in regional climate research for the Baltic Sea basin. These include climate changes since the last glaciation (approx. 12,000 years ago), changes in the recent past (the last 200 years), climate projections up until 2100 using state-of-the-art regional climate models and an assessment of climate-change impacts on terrestrial, freshwater and marine ecosystems. There are dedicated new chapters on sea-level rise, coastal erosion and impacts on urban areas. A new set of chapters deals with possible causes of regional climate change along with the global effects of increased greenhouse gas concentrations, namely atmospheric aerosols and land-cover change. The evidence collected and presented in this book shows that the regional climate has already started to change and this is expected to continue. Projections of potential future climates show that the region will probably become considerably warmer and wetter in some parts, but dryer in others. Terrestrial and aquatic ecosystems have already shown adjustments to increased temperatures and are expected to undergo further changes in the near future. The BACC II Author Team consists of 141 scientists from 12 countries, covering various disciplines related to climate research and related impacts. BACC II is a project of the Baltic Earth research network and contributes to the World Climate Research Programme.
Long-term Climate Change: Climatic Change during the Holocene (Past 12,000 Years) -- The Historical Timeframe (Past 1000 Years) -- Recent Climate Change (Past 200 years): Recent Change – Atmosphere -- Recent Change – River Runoff -- Recent Change – Terrestrial Cryosphere -- Recent Change – Marine Circulation and Stratification -- Recent Change – Sea Ice -- Recent Change – Sea Level and Wind Waves -- Future Climate Change: Projected Change – Models and Methodology -- Projected Change – Atmosphere -- Projected Change – Hydrology -- Projected Change – Marine Physics -- Projected Change – Sea Level -- Environmental Impacts of Climate Change: Environmental Impacts – Atmospheric Chemistry -- Environmental Impacts – Coastal Ecosystems, Birds and Forests -- Environmental Impacts – Freshwater Biogeochemistry -- Environmental Impacts – Marine Biogeochemistry -- Environmental Impacts – Marine Ecosystems -- Environmental Impacts – Coastal Erosion and Changing Coastlines -- Socio-Economic Impacts of Climate Change: Socio-Economic Impacts – Forestry and Agriculture -- Socio-Economic Impacts – Urban Settlements -- Drivers of Regional Climate Change: Evidence of Warming -- Regional Change Drivers – Aerosols -- Regional Change Drivers – Land Cover.
Keywords: Physical geography; Atmospheric sciences; Earth System Sciences; Atmospheric Sciences